KARAKTERISTIK FISIKOKIMIA ANTOSIANIN EKSTRAK KULIT BUAH NAGA MERAH MENGGUNAKAN METODE UAE (Physicochemical Characteristics of Red Dragon Fruit Skin Anthocyanin Extracts using UAE Method): Physicochemical Characteristics of Dragon Fruit Peels (Hylocereus polyrhizus) Anthocyanin Extracts using UAE (Ultrasound Assisted Extraction) Method - Asri Widyasanti; Novira Nurlaily; Endah Wulandari (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Dragon fruit peel (Hylocereus polyrhizus) contains anthocyanin which can be used as a potential natural colorant. Anthocyanins can be taken through the extraction process. The extraction of anthocyanin was performed by UAE (Ultrasound Assisted Extraction) method. UAE was chosen because it can result greater extraction efficiency and shorter operating times compared to conventional method. This study aims was to determine the effects of different amplitude and extraction times on the characteristics of dragron fruit peels extract using UAE. The control used was maceration method. The operating amplitude were evaluated at two levels 65% and 95%. Ultrasonic processor of 500 W output with frequency 20 kHz, solid-solvent ratio 1: 20, 60 mesh particle size with 15 minutes, 30 minutes and 45 minutes extraction times. The solvent used was aquadest with citric acid 10%. The method used was laboratory experiments using descriptive analysis. Characteristics of dragron fruit peel extracts investigated were total yield, residual solvent content, specific gravity, total anthocyanin, pH, and colour characteristics. The results showed that the dragon fruit peel extracts with amplitude 65% and extraction time of 45 minutes was the best treatment with total yield 10.62%, residual solvent content 37.50%, spesific gravity 1.2198, total anthocyanin content 29.640 ppm, pH 2.80, respectively. Based on hue angle (23.42o) the dragon fruit peel extracts obtained was resulting in red colour. Meanwhile, control treatment revealed that total yield was 9.44%, residual solvent content was 52.67%, spesific gravity 1.0609, total anthocyanin content 24.074 ppm, pH 3.06, and hue angle 33.16 o. It proven that UAE could increase the effectiveness of anthocyanin extraction and reduce residual solvent content of dragon fruit peel extracts compared to maceration. Hence, the present study makes influences of ultrasound technique on physico-chemical characteristics during extraction.